2022
DOI: 10.1039/d2ee02121h
|View full text |Cite
|
Sign up to set email alerts
|

Ampere-level CO2reduction to multicarbon products over a copper gas penetration electrode

Abstract: Renewable energy-driven electrochemical CO2 conversion to value-added chemicals is a prospective strategy for addressing both carbon emission and energy consumption. Although considerable progress has been made in CO2 electroreduction, sustained...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 73 publications
0
25
0
Order By: Relevance
“…The CO 2 RR is a typical gas-phase reaction that requires efficient capture and activation of CO 2 molecules to produce valuable chemicals . To achieve this, an effective photoelectrode should possess specific catalytically active sites for CO 2 reduction products and promote the diffusion of CO 2 molecules. , Several strategies, such as morphology manipulation, , particle size tuning, , and formation of multimetallic alloys, , have been implemented to improve the CO 2 reduction selectivity and suppress the competing HER. In addition to the catalyst itself, the properties of the photoelectrode/electrolyte interface are also critical to enhance the CO 2 reduction activity of the photoelectrode.…”
mentioning
confidence: 99%
“…The CO 2 RR is a typical gas-phase reaction that requires efficient capture and activation of CO 2 molecules to produce valuable chemicals . To achieve this, an effective photoelectrode should possess specific catalytically active sites for CO 2 reduction products and promote the diffusion of CO 2 molecules. , Several strategies, such as morphology manipulation, , particle size tuning, , and formation of multimetallic alloys, , have been implemented to improve the CO 2 reduction selectivity and suppress the competing HER. In addition to the catalyst itself, the properties of the photoelectrode/electrolyte interface are also critical to enhance the CO 2 reduction activity of the photoelectrode.…”
mentioning
confidence: 99%
“…It is believed that there are mainly two reaction routes for C 2+ production: activated CO 2 on the catalyst surface is first converted into absorbed CO, and then two *CO intermediates would form *COCHO and following *CHOCHO or form *COCOH and following *CHCOH. 56,57 In this work, the use of Cu-based catalysts with different oxidation states is intended to indicate the applicability of the in situ reconstruction method of first phosphate buffer treatment and then electroreduction to obtain phosphatederived copper catalysts. All Cu-based catalysts experienced a similar reconstruction process, indicating that the Cu-based catalysts could react with the phosphate buffer to form copper phosphate nanosheets and then back into highly dispersed Cu nanoparticles, regardless of what the original oxidation state of Cu, and all exhibited the promoted CO 2 ERR performances toward C 2+ productions.…”
Section: Resultsmentioning
confidence: 99%
“…8a) conrmed a signicant enhancement in the adsorption of *CO on the Cu(100) facet, enabling efficient C-C coupling and yielding a remarkable selectivity of 62.8% towards C 2+ products at an ultra-high current of 2.3 A cm −2 , surpassing that of existing Cu-based catalysts. 168 Several recent studies have reported the enhanced adsorption of *CO on Cu(100) and Cu(110) crystalline surfaces. [169][170][171] The synergistic effect of different crystalline sites is worth considering to modulate the behaviour of reaction intermediates.…”
Section: Facetmentioning
confidence: 99%